2020
DOI: 10.2174/1872210513666191204111006
|View full text |Cite
|
Sign up to set email alerts
|

CNTs Supercapacitor Based on the PVDF/PVA Gel Electrolytes

Abstract: : In this paper, the supercapacitor based on the carbon nanotubes (CNTs) electrodes has been fabricated. The polyvinylidene fluoride (PVDF) and polyvinyl alcohol (PVA) were used as a gel electrolyte. The electrodes and electrolytes thin films were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The specific capacitance (Cs) of the CNTs-based supercapacitor has been measured using the cyclic voltammetry and galvanostatic methods. For the scan rate, 20 mV s-1 the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Such rate performance difference is consistent with the EIS testing results. Additionally, the energy density and power density of MPCNF-750 in the current density of 0.2 A g −1 are 33.6 Wh kg −1 and 295.6 W kg −1 , respectively, according to the reported method of calculation [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such rate performance difference is consistent with the EIS testing results. Additionally, the energy density and power density of MPCNF-750 in the current density of 0.2 A g −1 are 33.6 Wh kg −1 and 295.6 W kg −1 , respectively, according to the reported method of calculation [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…11 A paper supercapacitor with graphite nanoparticles and different types of gel electrolytes such as polyvinyl alcohol (PVA)/phosphoric acid (H 3 PO 4 ) and polyvinylidene fluoride (PVDF) was fabricated with a BaTio 3 separator film, which showcased a specific capacitance of about 312 F g −1 . 12 A CNT-based supercapacitor 13 and BaTiO 3 /PEDOT-based ultracapacitor on a paper substrate with a PSS separator film also showed excellent electrochemical behavior. 14 A literature review of high-performance supercapacitors revealed that one of the most common metal oxide electrode materials is RuO 2 .…”
Section: Introductionmentioning
confidence: 95%
“…5,[12][13][14][15] In terms of electrostatic double-layer capacitors, their capacitance mainly comes from the separation of electric charge at the interface between the electrode and electrolyte, whereas the capacitance of faradaic pseudo-capacitors is created by the high-reversible faradaic redox reaction at the electrode surface. 5,[16][17][18][19] Carbonbased materials such as carbon nanotubes 20,21 and graphene 22 have been frequently used as electrodes for electrostatic double-layer capacitors because they have a high specific area and electrical conductivity. Moreover, metal oxides are always used as the electrodes for faradaic pseudocapacitors given that they are redox-active materials.…”
Section: Introductionmentioning
confidence: 99%